Co-Creating the Real: A Transdisciplinary Dialogue. (June 2022) - Glăveanu, Vlad P.; de Miranda, Luis
This article is the fruit of a written dialogue between a sociocultural psychologist and a philosopher invested in the study of the Creative Real, in a context that resonates with process philosophy and posthumanism. Each of the two authors come from a different tradition (or, rather, different traditions) to the topic of posthuman creativity and their approaches overlap considerably but include as well important points of difference, ranging from writing style to key concepts and areas of application.